Pendampingan Pembuatan Laporan Keuangan Sederhana Pada Usaha Keripik Di Kelurahan Tassililu Kec. Sinjai Barat - Nuraeni Nuraeni; Hardiyanti Ridwan; Satria Ramli; Andi Alauddin; Chaerul Sani (ABDI DAYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The information in a financial report is a visual representation of a company's financial performance as well as its financial condition. As a result, financial reports can be considered an important tool for obtaining information about a company's performance results as well as its financial position. The observation method and the socialization method are utilized in the execution of community service. Students are able to assist business actors in the preparation of straightforward financial reports for chip companies, particularly Rezky Chips and Lamolo Chips, as a result of this community service project. Business actors have begun to realize the significance of a company's financial reports following this assistance. Since the benchmark for the outcome of a business can likewise be seen from its very much organized and clear monetary reports.